Bibliometric Analysis of Algal-Bacterial Symbiosis in Wastewater Treatment - Qi, Yun (Int J Environ Res Public Health, 2019)
In recent years, the algae-bacteria symbiotic system has played a significant role in the sustainable development of wastewater treatment. With the continuous expansion of research outputs, publications related to wastewater treatment via algal-bacterial consortia appear to be on the rise. Based on SCI-EXPANDED database, this study investigated the research activities and tendencies of algae-bacteria symbiotic wastewater treatment technology by bibliometric method from 1998 to 2017. The results indicated that environmental sciences and ecology was the most productive subject categories, followed by engineering. Bioresource Technology was the most prominent journal in this field with considerable academic influence. China (146), USA (139) and Spain (76) had the largest amount of publications. Among them, USA was in a leading position in international cooperation, with the highest h-index (67) in 79 countries/territories. The cooperation between China and USA was the closest. The cooperative publishing rate of the Chinese Academy of Sciences was 83.33%, but most of them were in cooperation with domestic institutions, while international cooperation was relatively limited. Methane production, biofuel production, and extracellular polymeric substance were future focal frontiers of research, and this field had gradually become a multi-perspective and inter-disciplinary approach combining biological, environmental and energy technologies.